2017
DOI: 10.5194/acp-17-12303-2017
|View full text |Cite
|
Sign up to set email alerts
|

Emission ratios of trace gases and particles for Siberian forest fires on the basis of mobile ground observations

Abstract: Abstract. Boreal forest fires are currently recognized as a significant factor in climate change and air quality problems. Although emissions of biomass burning products are widely measured in many regions, there is still lack of information on the composition of wildfire emissions in Siberia, a region known for its severe wildfire activity. Emission ratios (ERs) are important characteristics of wildfire emissions as they may be used to calculate the mass of species emitted into the atmosphere due to combustio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 120 publications
1
15
0
Order By: Relevance
“…Analysis of these data indicates that smoldering processes may have a higher contribution to total wildfire emissions from North American boreal forests than previous estimates derived from aircraft sampling. To quantify the spatial and temporal variability of individual fires and their influence on CO, CH 4 , and CO 2 at the CRV tower, we coupled a fire emissions inventory, the Alaska Fire Emissions Database (AKFED) (Veraverbeke et al, 2015), with an atmospheric transport model, the Polar Weather Research and Forecasting Stochastic Time Integrated Lagrangian Transport (PWRF-STILT) model (Henderson et al, 2015). This modeling analysis indicated that the number of 2015 wildfires sampled in our study is comparable to the total number of North American boreal forest fires sampled in past work.…”
Section: Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Analysis of these data indicates that smoldering processes may have a higher contribution to total wildfire emissions from North American boreal forests than previous estimates derived from aircraft sampling. To quantify the spatial and temporal variability of individual fires and their influence on CO, CH 4 , and CO 2 at the CRV tower, we coupled a fire emissions inventory, the Alaska Fire Emissions Database (AKFED) (Veraverbeke et al, 2015), with an atmospheric transport model, the Polar Weather Research and Forecasting Stochastic Time Integrated Lagrangian Transport (PWRF-STILT) model (Henderson et al, 2015). This modeling analysis indicated that the number of 2015 wildfires sampled in our study is comparable to the total number of North American boreal forest fires sampled in past work.…”
Section: Studymentioning
confidence: 99%
“…We coupled a fire emission model, the Alaskan Fire Emissions Database (AKFED) (Veraverbeke et al, 2015), with an atmospheric transport model, the Polar Weather Research and Forecasting Stochastic Time Integrated Lagrangian Transport model (PWRF-STILT) (Henderson et al, 2015), to estimate fire contributions to trace gas variability at the CRV tower, following Wiggins et al (2016). For this application, STILT (Lin et al, 2007) was used to estimate the adjoint of PWRF (Skamarock et al, 2005;Chang et al, 2014;Henderson et al, 2015) during the summer of 2015 at the location of the CRV tower to generate surface influence functions that relate surface ecosystem fluxes from Alaska to trace mole fractions at CRV.…”
Section: Transport Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…The modern TROICA mobile railroad laboratory, which was manufactured in 2004 after a special design, is equipped with high-precision instruments intended for monitoring the gas and aerosol composition of the atmosphere and the radiative and meteorological characteristics and also for monitoring the soil, water, and vegetation pollution. At present, the laboratory is able of continuous real-time monitoring the concentrations of ozone (O 3 ), nitrogen oxides (NO and NO 2 ), carbon oxides (CO and CO 2 ), methane (CH 4 ) and a sum of non-methane hydrocarbons (NMHC), sulfur dioxide (SO 2 ), ammonia (NH 3 ), about 30 volatile organic compounds (VOCs), and radon ( 222 Rn) and its decay products, the mass and number concentrations of aerosol particles (including soot) in the size range from 2 nm to 15 µm, and the entire spectrum of meteorological parameters and solar-radiation characteristics with a high temporal resolution (from 10 s to 20 min), see (Berezina et al 2013), , (Vasileva et al 2017). As a result of cooperation between a number of Russian and world scientific centers, a series of 15 international experiments on observations of the state of the atmosphere over vast Russian regions, from Moscow to Vladivostok and from Murmansk to Kislovodsk, was performed.…”
Section: Introductionmentioning
confidence: 99%